Association of erythrocyte methotrexate-polyglutamate levels with the efficacy and hepatotoxicity of methotrexate in patients with rheumatoid arthritis: a 76-week prospective study. Issue 1 (3rd January 2017) - Takahashi, Chihiro; Kaneko, Yuko; Okano, Yutaka; Taguchi, Hiroaki; Oshima, Hisaji; Izumi, Keisuke; Yamaoka, Kunihiro; Takeuchi, Tsutomu
Abstract : Objective: To assess the utility of erythrocyte methotrexate-polyglutamate (MTX-PG) concentrations in determining the safety and efficacy of MTX in patients with rheumatoid arthritis (RA). Methods: 79 MTX-naïve patients with RA were enrolled in this prospective 76-week cohort study. MTX was initiated, and a predefined dose-escalation protocol was followed. Erythrocyte MTX-PG concentrations were measured using liquid chromatography. The associations of MTX-PG concentrations with disease activity and adverse events were analysed. Results: Dose escalation of MTX resulted in increased MTX-PG concentrations and a decrease in the mean Disease Activity Score in 28 joints (DAS28). A significant association was observed between total MTX-PG concentrations and ΔDAS28 at week 12 (β=−0.013, p=0.003) and at week 24 (β=−0.014, p=0.003). The maximum MTX-PG levels were significantly higher in patients presenting with elevated transaminases (≥100 IU/L) than in those without (146 vs 106 nmol/L, p=0.009). Receiver operating characteristic curve analysis revealed that a total MTX-PG concentrations of 83 nmol/L at week 12 was the threshold for a DAS28 improvement of ≥1.2 at week 24, and 105 nmol/L was the threshold for transaminases of ≥50 IU/L and 131 nmol/L for transaminases of ≥100 IU/L. MTX-PG concentrations were strongly influenced by body mass index and a serum albumin level. Conclusions: MTX-PG concentrations are a useful biomarker in MTX therapy, in terms of efficacy and safety.